(untitled) ([Washington, D. C], 1976)
The book is the proceeding of The National Conference on Levels and Patterns of Professional Training in Psychology that took place in the summer of 1973. The Vail Conference began the process of dealing with the central issue: "What is the journeyperson entry level into professional psychology?" It took a stab at what a likely answer might be: Master's-level training, developed through programs characterized by strict quality control, can provide the required skills and competencies. It opened the door to a reconceptualization of professional psychology as a multilevel applied discipline that is held together simultaneously by a scientific discipline and by an underlying psychological service orientation cast in a framework of a fluid career lattice
Keywords: Psychology,Psychology; Study and teaching ( graduate ),Education